Metode Balancing Jig Procedure pada Tab Elevator Pesawat Boeing 737-800 untuk Mengurangi Dampak Flutter - Lalu Giat Juangsa Putra; Dian Saputra; Achmad Zahir Saputra (Politeknik Negeri Batam, 2018)
Primary flight control in aircraft consist of aileron, rudder and elevator, secondary flight control consist of flaps, slats, spoiler and trim tab. Before aircraft in flight, the primary and secondary flight con trol must be confirmed in balanced condition. If in unbalanced condition, flutter will occur when aircraft in flight. Flutter is an aeroelasticity phenomenon, it is a vibration phenomenon that caused aircraft wings